Shadow ticket [large type] - Pynchon, Thomas (Random House Large Print, 2025)
"Milwaukee 1932, the Great Depression going full blast, repeal ofProhibition just around the corner, Al Capone in the federal pen, the private investigation business shifting from labor-management relations to the more domestic kind. Hicks McTaggart, a one-time strikebreaker turned private eye, thinks he's found job security until he gets sent out on what should be a routine case, locating and bringing back the heiress of a Wisconsin cheese fortune who's taken a mind to go wandering. By the time Hicks catches up with her he will find himself entangled with Nazis, Soviet agents, British counterspies, swing musicians, practitioners of the paranormal, outlaw motorcyclists, and the troubles that come with each of them"--